KONSTITUSI SEBAGAI CERMIN IDENTITAS NASIONAL DALAM KAJIAN HISTORIS, SOSIOLOGIS, DAN POLITIK - Ismail, Sachiko Aqila Naila; Nindiatma, Bintang Asmaracha (FPIPSKR Universitas PGRI Semarang, 2025)
The constitution has a fundamental role in the life of the nation and state, regulating the system of government, the relationship between the state and citizens, and the protection of human rights. The development of the Indonesian constitution underwent various changes influenced by historical, social and political factors. From the 1945 Constitution passed at independence, the 1949 RIS Constitution, the 1950 UUDS, to returning to the 1945 Constitution through the 1959 Presidential Decree, each change reflected the political dynamics that occurred. The 1998 reforms were an important turning point with four amendments to the 1945 Constitution aimed at strengthening democracy and the rule of law. Social dynamics have also contributed to constitutional reform, especially in raising awareness of human rights and decentralizing governance. Meanwhile, political factors often determine the direction of constitutional change, especially through the role of political parties, governments and power elites. This research uses the literature study method with literature analysis to understand more deeply how historical, social and political factors influence the Indonesian constitution. The results show that the constitution has always evolved in response to changing times, but its implementation still faces various challenges. Therefore, a strong commitment from all elements of the nation is needed to ensure that the constitution can function effectively in creating a democratic, stable and equitable government.